Additive-modified all-inorganic perovskite solar cell and preparation method and application thereof

By using 6-hydroxy-2-naphthalene sulfonic acid alkali metal salt additive in all-inorganic perovskite solar cells to passivate the film defects, the problem of small grains and large grain boundaries of perovskite films is solved, and the photoelectric conversion efficiency is improved and stability, achieving more efficient photoelectric conversion and humidity stability.

CN119300549APending Publication Date: 2025-01-10GUANGDONG UNIV OF TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411193038.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-28
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The perovskite thin film of all-inorganic perovskite solar cells has small grains and a large grain boundary, which leads to non-radiative recombination of charges, which seriously affects the photoelectric conversion efficiency and stability.

Method used

The 6-hydroxy-2-naphthalene sulfonic acid alkali metal salt additive is introduced into the all-inorganic perovskite precursor solution, and the naphthalene ring promotes the charge carrier current by passivating electron-rich defects and grain boundary defects through alkali metal ions and -OH groups. The extraction of the cells and the growth of the film crystallization improve the crystal quality and stability of the film.

Benefits of technology

Effectively regulate the crystal growth of all-inorganic perovskite films, reduce defects, improve photoelectric conversion efficiency and humidity stability, enhance the stability of perovskite crystal phase structure, and improve photoelectric conversion efficiency and device stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119300549A_ABST
    Figure CN119300549A_ABST
Patent Text Reader

Abstract

The invention discloses an all-inorganic perovskite solar cell and a preparation method and application thereof, and belongs to the technical field of solar cells. According to the application of the 6-hydroxy-2-naphthalene sulfonic acid alkali metal salt in the all-inorganic perovskite solar cell additive, alkali metal cations are potassium ions and / or sodium ions. A 6-hydroxy-2-naphthalene sulfonic acid alkali metal salt additive is introduced into an all-inorganic perovskite precursor solution, has alkali metal cations, sulfonic acid groups, hydroxyl and naphthalene rings, and can synergistically passivate the surface and interface of an all-inorganic perovskite film. Alkali metal cations enter perovskite crystal lattices, so that the stability of a perovskite crystal phase structure is enhanced. By introducing the 6-hydroxy-2-naphthalene sulfonic acid alkali metal salt with proper concentration, the crystal quality of the film can be improved, the grain size can be increased, the grain boundary can be reduced, the service life of a carrier can be prolonged, charge recombination in the film can be reduced, and the photoelectric conversion efficiency of the full-inorganic perovskite solar cell and the humidity stability of a device can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of solar cells, and in particular relates to an additive-modified all-inorganic perovskite solar cell and a preparation method and application thereof. Background Art

[0002] Perovskite solar cells (PSCs) have developed rapidly in recent years. Since Miyasaka's team first reported a perovskite solar cell with an efficiency of 3.8% in 2009, after continuous in-depth exploration by researchers, organic-inorganic hybrid perovskite solar cells have now achieved higher efficiencies. However, the organic cation methylamine ion (MA) in the organic-inorganic hybrid perovskite material is + ), FA + ) are volatile in high temperature environments and have poor stability, which seriously hinders their commercial application. + ) replaces MA + and FA + The all-inorganic perovskite material prepared by organic ions as the light-absorbing layer can greatly improve the stability of PSCs. In the all-inorganic perovskite material, the X site is a halogen element, and the most common one is I - and Br - Therefore, many researchers have turned their attention to all-inorganic perovskite solar cells, which have a suitable bandgap width (1.92eV), not only have a good absorption spectrum, but also have good stability, and have great application potential in the field of photovoltaic devices. However, the perovskite film of all-inorganic perovskite solar cells has small grains, many grain boundaries, and many defects on the surface and grain boundaries. These defects can lead to non-radiative recombination of charges, which seriously affects the photoelectric conversion efficiency and stability of PSCs.

[0003] CN 115513318A discloses a method based on NH 4 All-inorganic CsPbBr regulated by Cl addition 3 Perovskite solar cells and their applications. 2 Add NH 4 Cl, the gas produced by the decomposition of ammonium chloride during annealing regulates PbBr 2 The porosity in the film makes the reaction more thorough and is conducive to the growth of large perovskite grains. Chloride ions can passivate halogen vacancy defects and improve the photoelectric efficiency. However, the photoelectric efficiency is only 9% to 11%, and the stability of all-inorganic perovskite solar cells has not been paid attention to. Summary of the invention

[0004] In order to overcome the problems existing in the above-mentioned prior art, the purpose of the present invention is to provide the application of 6-hydroxy-2-naphthalenesulfonic acid alkali metal salt in all-inorganic perovskite solar cells.

[0005] Another object of the present invention is to provide an all-inorganic perovskite solar cell additive.

[0006] Another object of the present invention is to provide an all-inorganic perovskite solar cell.

[0007] Another object of the present invention is to provide a method for preparing an all-inorganic perovskite solar cell.

[0008] Another object of the present invention is to provide an application of an all-inorganic perovskite solar cell in the preparation of a battery module and a power station.

[0009] In order to achieve the above object, the present invention adopts the following technical solution:

[0010] Application of alkali metal salts of 6-hydroxy-2-naphthalenesulfonic acid in additives for all-inorganic perovskite solar cells.

[0011] Specifically, the alkali metal ion in the alkali metal salt of 6-hydroxy-2-naphthalenesulfonic acid is at least one of potassium ion and sodium ion.

[0012] The present invention introduces 6-hydroxy-2-naphthalenesulfonate additive into the all-inorganic perovskite precursor solution. The metal ions and -OH groups with strong electron-donating ability are helpful to passivate the electron-rich defects and grain boundary defects in the all-inorganic perovskite film. The sulfonic acid (-SO 3 - The negative electrostatic potential region around the ) group with strong electronegativity can serve as a potential chelating site to uncoordinated Pb 2+ Ionic interaction and strong π-π conjugation of the naphthalene ring contribute to the effective extraction of charge carriers, and the naphthalene ring is hydrophobic, which is beneficial to improving the humidity stability of all-inorganic perovskite solar cells. The four work together to effectively regulate the crystallization growth process and defect passivation of all-inorganic perovskite films, thereby improving the crystallization quality, photoelectric conversion efficiency and stability of all-inorganic perovskite films.

[0013] By adding sodium 6-hydroxy-2-naphthalenesulfonate as an additive to the all-inorganic perovskite precursor solution, alkali metal ions can enter the perovskite lattice, enhance the stability of the perovskite crystal phase structure, effectively improve the crystallization quality of the all-inorganic perovskite film, and improve the photoelectric conversion efficiency.

[0014] An all-inorganic perovskite solar cell additive comprises: 6-hydroxy-2-naphthalenesulfonic acid alkali metal salt.

[0015] Specifically, the concentration of the 6-hydroxy-2-naphthalenesulfonic acid alkali metal salt is 0.5 to 3 mg / mL.

[0016] An all-inorganic perovskite solar cell, whose device structure is arranged from bottom to top in sequence: a transparent conductive substrate, an electron transport layer, an all-inorganic perovskite light-absorbing layer and a carbon electrode; the all-inorganic perovskite light-absorbing layer includes an alkali metal salt of 6-hydroxy-2-naphthalenesulfonic acid.

[0017] Specifically, the molar ratio of the 6-hydroxy-2-naphthalenesulfonic acid alkali metal salt to the all-inorganic perovskite light-absorbing layer is (0.0018-0.0122): (1.0-1.4).

[0018] Specifically, the all-inorganic perovskite light-absorbing layer is CsPbI 2 Br, CsPbBr 3 , CsPbI 3 , CsPbIBr 2 One of them.

[0019] Specifically, the thickness of the all-inorganic perovskite light-absorbing layer is 300-600 nm.

[0020] Specifically, the electron transport layer includes a first electron transport layer and a second electron transport layer.

[0021] The use of a composite double electron transport layer in carbon-based all-inorganic perovskite solar cells has reliable interface stability, better electron mobility and superior charge extraction capability, simple preparation process and reduced preparation cost.

[0022] More specifically, the first electron transport layer and the second electron transport layer are ZnO, SnO 2 、TiO 2 At least one of .

[0023] Specifically, the thickness of the electron transport layer is 40-60 nm.

[0024] Specifically, the transparent conductive substrate is one of FTO and ITO.

[0025] A method for preparing an all-inorganic perovskite solar cell comprises the following steps:

[0026] S1: depositing a first electron transport layer on a conductive substrate;

[0027] S2: depositing a second electron transport layer on the first electron transport layer;

[0028] S3: adding 6-hydroxy-2-naphthalenesulfonic acid alkali metal salt to the all-inorganic perovskite solution, and preparing the all-inorganic perovskite light absorbing layer by spin coating;

[0029] S4: preparing a carbon-based counter electrode on the all-inorganic perovskite light-absorbing layer; and obtaining the all-inorganic perovskite solar cell.

[0030] Specifically, the concentration of the 6-hydroxy-2-naphthalenesulfonic acid alkali metal salt in the all-inorganic perovskite solution is 0.5 to 3 mg / mL.

[0031] Specifically, the concentration of the all-inorganic perovskite light absorbing layer components is 1.0-1.4M.

[0032] Specifically, the thickness of the transparent conductive substrate is 2.1-2.3 mm.

[0033] Specifically, the thickness of the carbon electrode is 10 to 30 μm.

[0034] During the preparation, the steps S1 to S4 also include annealing.

[0035] Specifically, the annealing conditions in steps S1 and S2 are annealing at 140° C. to 160° C. for 25 to 35 minutes.

[0036] Specifically, the annealing conditions in step S3 are annealing at 40° C. to 50° C. for 0.5 to 2 min, and then annealing at 250° C. to 270° C. for 4 to 6 min.

[0037] Specifically, the annealing condition in step S4 is annealing at 110° C. to 130° C. for 15 to 25 minutes.

[0038] Specifically, steps S1 and S2 are completed in an air environment; steps S3 and S4 are completed in a nitrogen glove box.

[0039] The present invention also protects the use of an all-inorganic perovskite solar cell in the preparation of a battery assembly or a power station.

[0040] Compared with the prior art, the present invention has the following beneficial effects:

[0041] Introducing 6-hydroxy-2-naphthalenesulfonate additives into the all-inorganic perovskite precursor solution, the organic small molecule salt has alkali metal cations, sulfonic acid groups, hydroxyl groups and naphthalene rings, which can synergistically passivate the surface and interface of the all-inorganic perovskite film. The alkali metal cations enter the perovskite lattice and enhance the stability of the perovskite crystal phase structure. Introducing 6-hydroxy-2-naphthalenesulfonate at an appropriate concentration can improve the crystal quality of the film, increase the grain size, reduce the grain boundaries, extend the carrier lifetime, reduce the charge recombination in the film, and improve the photoelectric conversion efficiency of the all-inorganic perovskite solar cell and the humidity stability of the device. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 Schematic diagram of the structure of an upright carbon-based all-inorganic perovskite solar cell.

[0043] Figure 2This is the molecular structure diagram of 6-hydroxy-2-naphthalenesulfonic acid alkali metal salt.

[0044] Figure 3 SEM images of the all-inorganic perovskite films of Example 2 and Comparative Example 1.

[0045] Figure 4 The JV curves of the devices prepared in the examples and comparative examples are shown in FIG.

[0046] Figure 5 Graphs showing water contact angles for Example 2 and Comparative Example 1.

[0047] Figure 6 This is a SEM image of the cross section of the all-inorganic perovskite solar cell in Example 2.

[0048] Figure 7 1 is the XRD diagram of the all-inorganic perovskite film of Examples 1 to 4 and Comparative Example 1. DETAILED DESCRIPTION

[0049] The present invention is further described below in conjunction with embodiments and comparative examples, which are only intended to better illustrate the present invention rather than to limit it. The enumerated embodiments are only preferred embodiments, not all. Changes, substitutions, modifications, etc. made by those skilled in the art without making creative work all belong to the protection scope of the present invention.

[0050] If the manufacturer of the reagents or instruments used is not indicated, they are deemed to be conventional products that can be purchased commercially.

[0051] The present invention prepares an all-inorganic perovskite solar cell, and the cell device structure is as follows from bottom to top: a transparent conductive substrate, an electron transport layer, an all-inorganic perovskite light absorbing layer and a carbon electrode, such as Figure 1 The all-inorganic perovskite light-absorbing layer includes an alkali metal salt of 6-hydroxy-2-naphthalenesulfonic acid as an additive. Its molecular formula is as follows Figure 2 shown.

[0052] Embodiments 1 to 4 provide an all-inorganic perovskite solar cell additive, including: potassium 6-hydroxy-2-naphthalenesulfonate.

[0053] Example 1

[0054] This embodiment provides an all-inorganic perovskite solar cell, and the preparation method thereof comprises the following steps:

[0055] S1: Cleaning the transparent conductive glass substrate;

[0056] In this example, FTO conductive glass is selected as the transparent conductive substrate;

[0057] The FTO conductive glass was ultrasonically cleaned in FTO cleaning agent, deionized water, anhydrous ethanol, acetone and isopropanol for 15 minutes in sequence, and then dried with nitrogen and subjected to ultraviolet ozone treatment for 15 minutes.

[0058] S2: preparing a first electron transport layer;

[0059] In this embodiment, ZnO is selected as the first electron transport layer;

[0060] S2.1: 0.2195 g zinc acetate dihydrate (C 4 H 10 O 6 Zn), 2mL ethylene glycol monomethyl ether (C 3 H 8 O 2 ) and 61.7 μL ethanolamine (C 2 H 7 NO) and stirred at room temperature for 12 h until completely dissolved to obtain a ZnO precursor solution, which was filtered with a 0.22 μm filter membrane before use;

[0061] S2.2: Spin-coat the ZnO precursor solution on the FTO conductive glass substrate obtained in step S1 and anneal. The spin-coating and annealing procedures are: spin at a rotation speed of 3500 rpm for 30 seconds and anneal at a temperature of 150° C. for 30 minutes to obtain a ZnO first electron transport layer.

[0062] S3: preparing a second electron transport layer;

[0063] In this embodiment, SnO 2 As a second electron transport layer;

[0064] S3.1: SnO purchased from Alfa Aesar 2 The hydrocolloid dispersion (product specification: 15wt%) was diluted with ultrapure water to 2.67wt%. Ultrasonic vibration was performed for 5 min to obtain SnO 2 The precursor dispersion was filtered with a 0.22 μm filter membrane before use;

[0065] S3.2: Place SnO 2 The precursor dispersion was spin-coated on the ZnO first electron transport layer obtained in step S2 and annealed. The spin-coating and annealing procedures were: spinning at a speed of 3000 rpm for 30 seconds and annealing at a temperature of 150°C for 30 minutes to obtain SnO 2 The second electron transport layer.

[0066] S4: Preparation of all-inorganic perovskite light absorbing layer;

[0067] In this embodiment, CsPbI 2Br as the all-inorganic perovskite light-absorbing layer;

[0068] S4.1: Weigh 0.2202g PbBr 2 、0.3118gCsI、0.2766gPbI 2 and 0.5 mg potassium 6-hydroxy-2-naphthalenesulfonate, add 1 mL dimethyl sulfoxide (DMSO) solution to prepare 1.2 M CsPbI 2 The Br precursor solution was heated and stirred on a heating table at 50 °C overnight until dissolved and filtered through a 0.22 μm filter membrane before use;

[0069] S4.2: CsPbI 2 The Br precursor solution was spin-coated on the SnO 2 The spin coating and annealing procedures are as follows: first, spin at 1000 rpm for 10 s, then spin at 3000 rpm for 40 s, then anneal at 45 °C for 1 min, and then anneal at 260 °C for 5 min to obtain CsPbI 2 Br inorganic perovskite light absorbing layer.

[0070] S5: preparation of carbon electrode;

[0071] In this embodiment, commercial carbon paste is used as the carbon electrode;

[0072] The commercial carbon slurry was scraped on the all-inorganic perovskite light-absorbing layer by a scraping method. The annealing procedure was: annealing at 120°C for 20 minutes to obtain a carbon electrode. After assembly, a carbon-based all-inorganic perovskite solar cell was obtained.

[0073] The steps S1, S2 and S3 are completed in an air environment (temperature 20-30°C, relative humidity 20-30%), and the steps S4 and S5 are completed in a glove box filled with nitrogen.

[0074] The concentration of potassium 6-hydroxy-2-naphthalenesulfonate in the all-inorganic perovskite solution is 0.5 mg / mL.

[0075] Example 2

[0076] This embodiment provides an all-inorganic perovskite solar cell, and the preparation method thereof is different from that of Embodiment 1 only in that 1 mg of potassium 6-hydroxy-2-naphthalenesulfonate is added to the all-inorganic perovskite precursor solution; the other steps remain unchanged.

[0077] The concentration of potassium 6-hydroxy-2-naphthalenesulfonate in the all-inorganic perovskite solution is 1 mg / mL.

[0078] Example 3

[0079] This embodiment provides an all-inorganic perovskite solar cell, and the preparation method thereof is different from that of Embodiment 1 only in that 2 mg of potassium 6-hydroxy-2-naphthalenesulfonate is added to the all-inorganic perovskite precursor solution; the other steps remain unchanged.

[0080] The concentration of potassium 6-hydroxy-2-naphthalenesulfonate in the all-inorganic perovskite solution is 2 mg / mL.

[0081] Example 4

[0082] This embodiment provides an all-inorganic perovskite solar cell, and the preparation method thereof is different from that of Embodiment 1 only in that 3 mg of potassium 6-hydroxy-2-naphthalenesulfonate is added to the all-inorganic perovskite precursor solution; the other steps remain unchanged.

[0083] The concentration of potassium 6-hydroxy-2-naphthalenesulfonate in the all-inorganic perovskite solution is 3 mg / mL.

[0084] Example 5

[0085] This embodiment provides an all-inorganic perovskite solar cell additive, including: sodium 6-hydroxy-2-naphthalenesulfonate.

[0086] This embodiment provides an all-inorganic perovskite solar cell, and the preparation method thereof is different from that of Embodiment 1 only in that 1 mg of sodium 6-hydroxy-2-naphthalenesulfonate is added to the all-inorganic perovskite precursor solution; the other steps remain unchanged.

[0087] The concentration of the sodium 6-hydroxy-2-naphthalenesulfonate in the all-inorganic perovskite solution is 1 mg / mL.

[0088] Comparative Example 1

[0089] This comparative example provides an all-inorganic perovskite solar cell, and the preparation method thereof is different from that of Example 1 only in that potassium 6-hydroxy-2-naphthalenesulfonate is not added to the all-inorganic perovskite precursor solution; the other steps remain unchanged.

[0090] Comparative Example 2

[0091] In this comparative example, an all-inorganic perovskite solar cell was prepared according to the steps of comparative example 1, except that the all-inorganic perovskite solar cell also had an interface modification layer between the electron transport layer and the all-inorganic perovskite layer. The ZnO / SnO 2 The electronic layer was subjected to interface modification treatment, and the spin coating and annealing procedures were: spin coating at a rotation speed of 3000 rpm for 45 s and annealing at 120°C for 10 min.

[0092] Performance Testing

[0093] The photoelectric conversion efficiency of the solar cell devices of the embodiment and the comparative example was tested using a Newport 150W Oriel 92252A solar simulator and a Keithley 2400 light source meter plus signal processing software as the test platform. The test conditions were standard simulated sunlight AM 1.5 (100mW / cm 2 ), temperature 20-30°C, relative humidity 20-30%. The effective area of ​​carbon-based all-inorganic perovskite solar cells is: 0.09cm 2 .

[0094] The solar cell prepared in Comparative Example 1 is marked as: Control.

[0095] The contact angle test was performed on the all-inorganic perovskite film of Example 2 and the all-inorganic perovskite film of Comparative Example 1.

[0096] Figure 3 a is CsPbI in Comparative Example 1 2 Surface SEM image of Br inorganic perovskite light-absorbing layer; Figure 3 b is CsPbI in Example 2 2 Surface SEM image of Br inorganic perovskite light absorbing layer. As can be seen from the figure, there are a lot of holes on the surface of the film of comparative example 1, and the grains are small. 2 The Br film has large grains, fewer grain boundaries, and no pinholes on the film surface, indicating that the additive helps the film grain growth and surface defect passivation of the all-inorganic perovskite light-absorbing layer.

[0097] Figure 4 The JV characteristic curves of the carbon-based all-inorganic perovskite solar cells in the embodiments of the present invention and the comparative examples are shown in Table 1. Table 1 shows the various photoelectric performance parameters corresponding to the JV characteristic curves, including: open circuit voltage (Voc), short circuit current density (Jsc), fill factor (FF) and photoelectric conversion efficiency (PCE).

[0098] Table 1 Photoelectric performance parameters of the devices prepared in the embodiments and comparative examples JV curves

[0099]

[0100] Depend on Figure 4 It can be seen from Table 1 that with the increase of additive concentration, the photoelectric conversion efficiency first increases and then decreases, and the optimal addition concentration is 1 mg / mL.

[0101] By comparison, it can be seen that the PCE of the carbon-based all-inorganic perovskite solar cell passivated with 6-hydroxy-2-naphthalenesulfonic acid alkali metal salt is improved, and the PCE is 13.23%, which is higher than 11.60% of Comparative Example 1.

[0102] In Comparative Example 2, potassium 6-hydroxy-2-naphthalenesulfonate is used as the interface modification layer. The photoelectric conversion efficiency of the device after interface modification is improved compared with the basic device, but its photoelectric conversion efficiency is not as good as the photoelectric conversion efficiency of the all-inorganic perovskite solar cell prepared by using potassium 6-hydroxy-2-naphthalenesulfonate as an additive.

[0103] Figure 5 The water contact angle diagrams of Comparative Example 1 and Example 2 of the present invention are shown in FIG. Figure 4 It can be seen that the water contact angle of Example 2 is greater than that of the comparative example, which indicates that the additive can improve the hydrophobicity of the all-inorganic perovskite film. The enhanced hydrophobicity improves the photoelectric conversion efficiency and humidity stability of the solar cell.

[0104] Figure 6 This is a SEM image of the cross section of the all-inorganic perovskite solar cell of Example 2. It can be seen from the figure that the thickness of the all-inorganic perovskite film is in the range of 300nm to 600nm.

[0105] Figure 7 The XRD diagrams of Examples 1 to 4 and Comparative Example 1 are shown in the figure. The right side is a partial enlarged view of the (200) crystal plane. Figure 7 It can be seen that with the increase of the addition amount, the deviation angle gradually increases, indicating that alkali metal ions can be partially incorporated into CsPbI 2 Br lattice, resulting in a slight shift in the diffraction peak position of the (200) crystal plane. When the addition concentration is 1 mg / mL, the characteristic peak diffraction peak intensity of the all-inorganic perovskite film is the strongest, indicating that the all-inorganic perovskite film has the best crystallinity.

[0106] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.

Claims

Application of alkali metal salts of 1.6-hydroxy-2-naphthalenesulfonic acid in additives for all-inorganic perovskite solar cells.

2. The use according to claim 1, characterized in that: The alkali metal ions in the 6-hydroxy-2-naphthalenesulfonic acid alkali metal salt are potassium ions and / or sodium ions.

3. An all-inorganic perovskite solar cell additive, characterized in that: include: 6-Hydroxy-2-naphthalenesulfonic acid alkali metal salt.

4. An all-inorganic perovskite solar cell, wherein the device structure is arranged from bottom to top in sequence: a transparent conductive substrate, an electron transport layer, an all-inorganic perovskite light absorption layer and a carbon electrode; characterized in that: The all-inorganic perovskite light-absorbing layer includes 6-hydroxy-2-naphthalenesulfonic acid alkali metal salt.

5. The all-inorganic perovskite solar cell according to claim 4, characterized in that: The molar ratio of the 6-hydroxy-2-naphthalenesulfonic acid alkali metal salt to the all-inorganic perovskite light-absorbing layer is (0.0018-0.0122): (1.0-1.4).

6. The all-inorganic perovskite solar cell according to claim 4, characterized in that: The all-inorganic perovskite light-absorbing layer is one of CsPbI2Br, CsPbBr3, CsPbI3, and CsPbIBr2.

7. The all-inorganic perovskite solar cell according to claim 4, characterized in that: The thickness of the all-inorganic perovskite light-absorbing layer is 300-600 nm.

8. A method for preparing an all-inorganic perovskite solar cell according to any one of claims 4 to 7, characterized in that: The steps include: S1: depositing a first electron transport layer on a conductive substrate; S2: depositing a second electron transport layer on the first electron transport layer; S3: adding 6-hydroxy-2-naphthalenesulfonic acid alkali metal salt to the all-inorganic perovskite solution, and preparing the all-inorganic perovskite light absorbing layer by spin coating; S4: preparing a carbon electrode on the all-inorganic perovskite light-absorbing layer; obtaining the all-inorganic perovskite solar cell.

9. The method for preparing an all-inorganic perovskite solar cell according to claim 8, characterized in that: The concentration of the 6-hydroxy-2-naphthalenesulfonic acid alkali metal salt in the all-inorganic perovskite solution is 0.5-3 mg / mL.

10. Use of the all-inorganic perovskite solar cell according to any one of claims 4 to 7 in the preparation of a battery module or a power station.

Citation Information

Patent Citations

  • Preparation method and application of high-quality all-inorganic perovskite thin film material

    CN109659394A

  • All-inorganic perovskite solar cell and preparation method thereof

    CN114242824A

  • Interface modified perovskite solar cell and preparation method thereof

    CN117156872A

  • Compound and use thereof in solar cell

    WO2023109035A1